Absence of relationship between MTTP haplotypes and longevity. - Neville, M; Clarke, R; Evans, J; Rubinsztein, D; Karpe, F (2007)
BACKGROUND: Polymorphisms for the microsomal triglyceride transfer protein (MTTP) gene have been associated with longevity and with lower risk for cardiovascular mortality. However, the association of MTTP with longevity has been contested in a large German collection of nonagenarians and centenarians. METHODS: We made a detailed characterization of MTTP haplotype carrier status in a cohort of 1398 old men and women (mean age 78 years) and a population-based cohort (n = 777) of younger controls (mean age 40 years) in Oxford, England. RESULTS: There were no significant differences in haplotypes for MTTP gene between the younger and older age groups. CONCLUSION: This study, which adopted a more detailed genetic analysis of the MTTP gene in a large case-control study of older people provides reliable evidence against any significant association of the MTTP gene with longevity.